Verificação dos efeitos genotóxicos dos agentes antineoplásicos citrato de tamoxifen e paclitaxel - Corrales, Edith Alba Luz Segovia (1997)
Cytotoxic chemotherapy has been routinely used in the treatment of neoplastic diseases since the 1950s. Although some types of tumors are refractory to this type of treatment, the prospect of survival for patients with some types of tumors has greatly increased in last years. Although this increase may be due to modern diagnostic methods, much is due to the use of chemotherapy (Ferguson and Pearson, 1996). A wide variety of antineoplastic agents are currently available on the market, with different modes of action, and most, if not all, have both mutagenic and carcinogenic effects. These agents may be alkylating (monofunctional and bifunctional); topo II inhibitors (DNA intercalating and non-intercalating); mitotic spindle inhibitors; antimetabolites; enzymes; sex hormones; hormonal antagonists; DNA cleaving agents (free radical generators) and agents that inhibit the immune response (Ferguson and Pearson, 1996). However, despite the success achieved with these agents, treatment with some of the most effective antineoplastic agents provides a traumatic patient experience, as well as a large number of symptoms of direct toxicity (Ferguson and Pearson, 1996). More and more descriptions of secondary cancer induction after anticancer chemotherapy are increasing. Less well documented are mutagenic sequelae, reflected as a variety of effects ranging from changes in fertility to cancer or birth defects in children of cancer survivors (Ferguson and Pearson, 1996)